"Close network" effect of a ZnO micro/nanoporous array allows high UV-irradiated NO2 sensing performance. Issue 34 (12th April 2017) - Su, Xingsong; Gao, Lei; Zhou, Fei; Cai, Weiping; Duan, Guotao
Abstract : The "close network" effect of a ZnO micro/nanoporous array allows high UV-irradiated NO2 sensing performance at room temperature. Abstract : ZnO micro/nanoporous arrays with controlled morphologies were fabricated by a monolayer colloidal crystal and solution-dipping strategy. Then their UV-irradiated NO2 sensing performances, especially the morpholgy-correlated effects were studied in detail. It was found that a close-network micro/nanoporous array film (CNPAF) and bowl-like micro/nanoporous array film (BLPAF), which were prepared with different concentrations of precursors, presented different sensing performances. The former showed higher sensitivity, lower detecting limit, and shorter response/recovery times. The "close network" effect was proposed to explain the mechanism behind these results. First, CNPAF has a closed network structure, which would decrease the resistance of the film and provide more sensing spots for NO2, which enhanced sensitivity. Second, according to the hydrokinetics of microluidic flow, the closed network structure may localize the flowing gas, which led to shorter response and recovery times of the sensor. This work clarified the morphology-correlated effect of ZnO micro/nanoporous arrays on their NO2 sensing performances, and it would be helpful for the realization of room temperature NO2 sensors.